Descripción De La Contribución De Los Ecosistemas Digitales A La Contabilidad (2023)
This work aims to describe the impact of digital ecosystems on accounting, currently emerging technologies are transforming the way accounting and business practices in general are carried out, digital ecosystems, in particular, They are enabling the creation of interconnected networks of companies, suppliers and customers that share information and resources in real time.